Exploring autoimmune endocrine diseases induced by monoclonal antibodies used as multiple sclerosis pharmacotherapy: a systematic review - Sahraian, Mohammad Ali; Emami, Shahaboddin; Ataei, Sara; Ghalandari, Nasibeh (Naunyn-Schmiedeberg's archives of pharmacology, 2025)
Multiple sclerosis (MS) is an autoimmune neurodegenerative disease that targets myelin, leading to inflammation and neuron death. Monoclonal antibodies (MAb) have long been used to control the progression and exacerbations of this disorder, which may induce secondary autoimmune disease as a rare adverse event. This systematic review aimed to gather data of case reports around this subject and to explain the mechanism behind their occurrence. PubMed, Scopus, and Google scholar were searched for published case reports until February 21st 2024. The Joanna Briggs Institute (JBI) critical appraisal checklist was used to assess the quality of the included studies. In total, 20 articles met the inclusion criteria and were reviewed by the authors. The most autoimmune disorders were thyroiditis and as expected induced by alemtuzumab. Ocrelizumab had one secondary autoimmune complication reported. MAbs used in MS immunotherapy have shown to induce secondary autoimmune disorders including endocrine complications, which have been reported in many case reports. It is recommended to use these agents with caution and monitor patients for symptoms of the aforementioned conditions.